PEMANTAUAN KUALITAS AIR SUMUR MENGGUNAKAN MULTIPROBE SENSOR DIGITAL DI WILAYAH SEKITAR SEMBURAN LUMPUR SIDOARJO - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2008)
Bursts of mud in Sidoarjo has caused changes in environmental quality around the bursts area. Observation in that area indicate there have been changes in air quality and odor caused by mud spurt. In addition, changes in the geological structure of land in the area around the mud spurt, has resulted some water spurt phenomenon that came from the well pump belong to some residensts in that area. This water spurt phenomenon is followed by the change of water quality which was to be used for the needs of daily living, now in some villages in the area around the mud bursts can no longer be used. To find out some parameters of water quality that arises from the some well pumps that produce big water spurt, we need to performed water quality monitoring using multiprobe digital sensors that are able to measure several parameters at once.This paper presents the measurement data of water quality in some well pumps that produce big water spurts with the YSI600R digital sensor.Ã‚Â Keywords : Perubahan kualitas lingkungan, semburan lumpur Sidoarjo, pemantuan kualitas air, sumber bubble, sumur pompa, sumur bor, separasi air dan gas, multi probe digital sensor